Hydrogen Sulfide Specifically Alters NAD(P)H Quinone Dehydrogenase 1 (NQO1) Olfactory Neurons in the Rat. (16th December 2017) - Imamura, Fumiaki; Cooper, Timothy K.; Hasegawa-Ishii, Sanae; Sonobe, Takashi; Haouzi, Philippe
Highlights: The distribution of NQO1 olfactory neurons in rats recapitulates that in mice. H2 S toxicity specifically affects NQO1 olfactory neuron expression. The present findings may be used to further study the function of these neurons. Abstract: The regions of the olfactory epithelium affected by hydrogen sulfide (H2 S) toxicity in the rat present a striking similarity with the developmental olfactory zone 1 described in the mouse. This zone which is the only region containing neurons expressing NAD(P)H quinone dehydrogenase 1 (NQO1) is involved in complex behavioral responses in rodents, and other mammals, triggered by specific olfactory stimuli. We therefore sought to determine whether (1) olfactory neurons expressing NQO1 are located in the same regions in the rats and in the mice and (2) there is an overlap between olfactory neurons expressing this protein and those affected by the toxicity of H2 S. Rats were exposed to H2 S – 200 ppm during 3 h, three consecutive days- and displayed symmetric acute segmental necrosis of the neurons and sustentacular cells of the olfactory epithelium in the dorsomedial nasal cavity. We found that expression of NQO1 in Sprague–Dawley rats spatially recapitulated that of the mouse. The degree of agreement or overlap between these two populations of neurons (necrosis vs. NQO1 expression) reached 80.2%. Although the underlying mechanisms accounted for the high sensitivity for NQO1 neurons -or the relative protection of non NQO1 neurons- to sulfide toxicity remain to be established, this observation is offering an intriguing approach that could be used to acutely suppress the pool of neural cells in olfactory zone I and to understand the mechanisms of toxicity and protection of other populations of neurons exposed to sulfide.